Empirical Assessment of Inflation Targeting (Analysis of Selected Economic Statistics) - Walerysiak, Grzegorz (Comparative Economic Research. Central and Eastern Europe, 2013)
Inflation Targeting (IT) is used by about 30 countries (both developed and developing countries) around the world, and the number of countries was said to increase (IMF 2005). IT strategy was created as a way of getting inflation under control. The global crisis of recent years has given a new perspective to IT strategy and its effectiveness. The most obvious way of analyzing the effects of IT is to compare characteristics of inflation for periods before and after its implementation. So in my research I try to answer following comparative aspects: First, how does IT strategy work, and second, how does it work in the situation of global turmoil? I analyzed the years before and after implementation of IT strategy for those countries which employ it, as well as its implementation and effect during the time of the global crises.